P262 Oramorph for breathlessness: in pursuit of guidelines and patient information for use in COPD. (2nd December 2011) - Williamson, A; Restrick, L; Potter, C; Purcell, S; Roberts, S; Coleman, B; Stern, M
Abstract : Introduction: Breathlessness is the most common and frightening symptom in Chronic Obstructive Pulmonary Disease (COPD). Short-acting morphine (Oramorph) has traditionally been used to treat breathlessness in palliative care. Although used in COPD (Simon et al, 2010), there is no consensus/guidelines for prescribing and patients stigmatise morphine, associating it with dying or addiction. In this study, we assessed current prescribing practice, patient use and safety of Oramorph, to inform local prescribing guidelines and patient information. Method: Case notes of patients who were prescribed Oramorph for breathlessness while having multidisciplinary COPD care between 2004 and 2011 were reviewed. The following were documented: patient demographics, disease severity (FEV1, MRC dyspnoea score, nebulisers, long term oxygen therapy (LTOT), domiciliary Non-Invasive Ventilation (NIV), social/healthcare support and palliative care referrals; Oramorph starting dosage, dosage range, increase in dosage, patient choice to continue, duration of and use of morphine sulphate slow release tablet (MST). Results: 28 COPD patients prescribed Oramorph for breathlessness were identified (14 M), median (range) age 70 (52–83) years FEV1 (mean±SD) 0.58±0.22, MRC dyspnoea score 4.6±0.49. 19/28 (68%) were on LTOT, 28/28 (100%) on nebulisers, 5/28 (17%) on domiciliary NIV, two current smokers, 10/28 (36%) lived alone, 27/28 (96%) had professional healthcare domiciliary visits, 8/28 (29%) had palliative care input. Starting, incremental and current dosing of Oramorph are shown in the Abstract P262 table 1 . 25/28 (89%) patients chose to stay on Oramorph once started. Median (range) duration on Oramorph was 8 months (45 days–7.5 years). MST was added for breathlessness in three patients. 13/28 (46%) patients died; all were MRC 5 and starting Oramorph was not felt to be a contributing factor by the clinical team. Time to death after starting Oramorph was median (range) 7 months (68 days–2.6 years). Oramorph prescribing in COPD increased year-on-year (one patient in 2004 to 12 in 2010). Conclusion: Oramorph prescribed by a respiratory team for breathlessness is safe in this group of patients. This study indicates that its effect is sustained despite low dosages with little requirement for incremental dosing over time. Guidelines for prescribing and patient information will be critical to ensure that patients are not denied this useful treatment of breathlessness.